Are Investors Beyond Rationality? Uncovering Behavioral Finance in Stock Investment Decision Making: A Comprehensive Systematic Literature Review - Valsa Ayunda Tisya (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
Humans have complex natures, cannot be predicted or followed by theory. The emotional and cognitive aspects that play a role in financial decision making, especially stock investment, are very important to study. The contribution of this theory will be very useful in mitigating the risk of biased decision making. This article is based on the Systematic Literature Review (SLR) method. This systematic literature review examines a large number of studies on behavioral finance from 11 leading and reputable financial journals published between 2020 and 2024. Articles are collected through Harzing's Publish or Perish with Scopus and Google Scholar article data sources. This SLR research uses the keywords